2011
DOI: 10.1007/s00421-011-1894-3
|View full text |Cite
|
Sign up to set email alerts
|

Muscle architecture and EMG activity changes during isotonic and isokinetic eccentric exercises

Abstract: The present study aimed to compare muscle architecture and electromyographic activity during isotonic (IT) and isokinetic (IK) knee extensors eccentric contractions. Seventeen subjects were assigned in test and reproducibility groups. During test session, subjects performed two IT and two IK sets of eccentric contractions of knee extensor muscles. Torque, angular velocity, VL architecture and EMG activity of agonist (vastus lateralis, VL; vastus medialis; rectus femoris) and antagonist (semitendinosus; biceps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 40 publications
3
49
0
3
Order By: Relevance
“…), especialmente do modo de treino (isométrico, concêntrico ou excêntrico) 27 . Guilhem et al 21 , que além de outras variáveis (torque, velocidade angular e arquitetura muscular), compararam a atividade da RMS do EMGs de extensores (VM, VL e RF) do joelho, na contração excêntrica isocinética versus isotônica, observaram uma menor amplitude do sinal eletromiográfico associada ao exercício isocinético. Embora estes achados se coadunem, em parte, com nossos resultados, eles não avaliaram o efeito do treino, nem fizeram a comparação entre contração excêntrica e isométrica.…”
Section: Tabelaunclassified
See 1 more Smart Citation
“…), especialmente do modo de treino (isométrico, concêntrico ou excêntrico) 27 . Guilhem et al 21 , que além de outras variáveis (torque, velocidade angular e arquitetura muscular), compararam a atividade da RMS do EMGs de extensores (VM, VL e RF) do joelho, na contração excêntrica isocinética versus isotônica, observaram uma menor amplitude do sinal eletromiográfico associada ao exercício isocinético. Embora estes achados se coadunem, em parte, com nossos resultados, eles não avaliaram o efeito do treino, nem fizeram a comparação entre contração excêntrica e isométrica.…”
Section: Tabelaunclassified
“…Eletromiografia de superfície (EMGs): Para o registro do sinal elétrico dos músculos vasto medial (VM), vasto lateral (VL), reto femoral (RF), semitendinoso (ST) e bíceps femoral (BF) 5,21 , foi utilizado um eletromiógrafo (modelo 800C, EMG System do Brasil) com as seguintes características técnicas: hardware com placa de conversão analógico-digital (A/D) de 12 bits; amplificador com ganho de 1000 vezes; filtro passa banda de 20 a 500 Hz (Butterworth de 2 a ordem); razão de rejeição de modo comum (RRMC) >100 dB; taxa de ruído do sinal < 3 µV RMS; impedância de 10 9 Ohms; eletrodos superficiais (bipolares, ativos) com pré-amplificação de 20 vezes e um software Aqdados para coleta e análise de sinais com frequência de amostragem de 1000 Hz, por canal, montado em plataforma Windows.…”
unclassified
“…The novelty of this pilot study is to use surface electyromyographic (EMG) activity to better explain putative changes associated with Ramadan. In fact, EMG activity can be used to assess neural drive during maximal voluntary contraction (Guilhem et al 2011) and to evaluate muscle fatigue during submaximal exercises as performed in numerous works (for review, see Cifrek et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Strains as large as 30 -50% relative to fascicle length (an estimate of L f) have been reported in vivo for human gastrocnemius muscles during dorsiflexion (41,16) and vastus lateralis muscles during knee flexion (12). Modeling studies incorporating subject data have also found that fascicles actively lengthened as much as 37% (splenius capitis) and 50% (semispinalis capitis) during low-velocity automobile impacts (46), and 64% near the myotendinous junction of the biceps femoris muscle (36).…”
Section: Animalsmentioning
confidence: 94%